Shaping the Spiritual World View of Adolescent Girls Based on Oriental Education - Makhmudova Muyassar; Kochkhorova Aysha Altibayevna (International Journal on Integrated Education, 2023)
In this article, the development of spiritual and moral consciousness of adolescent girls, self-awareness and improvement based on moral values, psychological conditions of modern adolescents, special attention to girls in Uzbek families, their national Based on the values, moral, honorable, thrifty, intelligent upbringing and educational activities carried out in families are described. Also, the role of the mother in the family and its relevance to the development of the society are highlighted.